Application of MoS2 thin film in multi-wavelength and Q-switched EDFL. Issue 5 (9th March 2017) - Ahmad, Harith; Aidit, Siti Nabila; Tiu, Zian Cheak; Ismail, Mohammad Faizal; Suthaskumar, Muneswaran; Harun, Sulaiman Wadi
Abstract: Multi-wavelength and Q-switched EDFLs are demonstrated using a MoS2 thin film as stabilizer and saturable absorber, respectively. For a multi-wavelength output, a 50-m-long PCF is incorporated into the cavity to induce unstable multi-wavelength oscillation and a MoS2 thin film is further incorporated into the cavity to achieve stable multi-wavelength. The laser generates 11 lasing wavelengths with constant spacing of 0.47 nm at pump power of 250 mW. In the case of the Q-switched EDFL, MoS2 thin film is utilized as a saturable absorber. Q-switched operation occurrs at a threshold pump power of 28.86–51.48 mW and the spectrum is centered at 1561.15 nm. The pulse repetition rate showed increasing trend from 18.57–30.72 kHz whereas the pulse width decreased from 53.85–32.54 μs in the Q-switched pump power range. The highest pulse energy of 30.73 nJ is obtained at pump power of 51.48 mW.